Exploring Project-Based Learning: Physics E-Posters in Pre-Service Science Education - Pranata, Ogi Danika; Sundari, Putri Dwi; Sulaiman, Dady (Universitas Islam Negeri (UIN) Mataram, 2023)
This study investigates the implementation of project-based learning, explicitly focusing on designing and presenting e-posters within the Basic Physics course for pre-service science teachers, with a particular emphasis on pre-service biology teachers. Descriptive and correlational quantitative methods were utilized to analyze data collected from 16 participating students throughout 16 sessions. The assessment perspectives of lecturers, peers, and self-assessment were examined, revealing disparities in scores and highlighting the importance of multiple assessment sources. Recognition through awards was granted to students with exemplary performance, while guidance sessions led by the instructor significantly correlated with improvements in poster design. Analysis of poster content indicated a focus on fundamental physics concepts, mainly mechanics, with students utilizing various information sources. The study underscores the effectiveness of project-based learning in promoting student engagement, skill development, and conceptual understanding in physics education.